2012
DOI: 10.1016/j.gpb.2012.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Homepeptide Repeats: Implications for Protein Structure, Function and Evolution

Abstract: Analysis of protein sequences from Mycobacterium tuberculosis H37Rv (Mtb H37Rv) was performed to identify homopeptide repeat-containing proteins (HRCPs). Functional annotation of the HRCPs showed that they are preferentially involved in cellular metabolism. Furthermore, these homopeptide repeats might play some specific roles in protein–protein interaction. Repeat length differences among Bacteria, Archaea and Eukaryotes were calculated in order to identify the conservation of the repeats in these divergent ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Our survey of long repeats in a non-redundant set of UniProt sequences has highlighted the occurrence of these repeats that play an important role in the structure and function of domains of the proteins. Previous studies have focused on structural and functional implications of proteins with homo repeats (Uthayakumar et al, 2012), fibrous repeats (Parry, 2005) and different well-characterized repeats of length 5–50 (Andrade et al, 2001). Therefore, an in-depth study of long repeats in UniProt sequences was carried out for a better understanding of the correspondence of repeat sequences with their structures and functions.…”
Section: Discussionmentioning
confidence: 99%
“…Our survey of long repeats in a non-redundant set of UniProt sequences has highlighted the occurrence of these repeats that play an important role in the structure and function of domains of the proteins. Previous studies have focused on structural and functional implications of proteins with homo repeats (Uthayakumar et al, 2012), fibrous repeats (Parry, 2005) and different well-characterized repeats of length 5–50 (Andrade et al, 2001). Therefore, an in-depth study of long repeats in UniProt sequences was carried out for a better understanding of the correspondence of repeat sequences with their structures and functions.…”
Section: Discussionmentioning
confidence: 99%
“…In general, homopeptides are more conserved in bacteria, than in archaea and eukaryotes, and there is a correlation between repeat length differences and species divergence (Uthayakumar et al 2012). Homopeptides increase the functional versatility of proteins, and facilitate spatial organization of proteins in a repeat-dependent way (Chavali et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although homopeptides are sites of such polymorphic variation, earlier work showed that some homopeptides are deeply conserved across orthologs from bacteria and eukaryotes, suggesting ancient origin and functional essentiality ( Faux et al, 2005 ). In general, homopeptides are more conserved in bacteria, than in archaea and eukaryotes, and there is a correlation between repeat length differences and species divergence ( Uthayakumar et al, 2012 ). Homopeptides increase the functional versatility of proteins, and facilitate spatial organization of proteins in a repeat-dependent way ( Chavali et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%